On Psychological Continuity and Dementia. Issue 1 (24th February 2023) - Holland, Tim
Abstract: This letter responds to the article "On the Authority of Advance Euthanasia Directives for People with Severe Dementia: Reflections on a Dutch Case, " by Henri Wijsbek and Thomas Nys, in the September‐October 2022 issue of the Hastings Center Report.